THE INFLUENCE OF MOTIVATION, ORGANIZATIONAL SUPPORT AND ORGANIZATIONAL CULTURE ON JOB SATISFACTION WITH COMMITMENT AS AN INTERVENING VARIABEL IN GOVERNMENT AGENCY EMPLOYEES : LITERATUR REVIEW - Putri, Dika Hardiyani; Hadi, Syamsul; Septyarini, Epsilandri (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This article aims to understand in depth through literature review the relationshipbetween motivation, organizational support, and organizational culture on jobsatisfaction with commitment as an intervening variable. The research method usedis a systematic literature review (SLR) using 37 articles obtained from the GoogleScholar database using the keywords